CONSUMER ACCEPTANCE STUDY OF BLOOD SHELL MEATBALLS (Anadara granosa) WITH DIFFERENT AMOUNT OF BINDER - Afrianto, Dodi; Sari, N.Ira; Dahlia, Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThis study aims to determine consumer acceptance of blood clam meatballs with different amounts of binder. The treatment consisted of (KD1) 50 g tapioca flour adding 500 g blood clam meat, (KD2) 75 g tapioca flour adding 500 g blood clam meat, (KD3) 100 g tapioca flour adding 500 g blood clam meat, and (KD4) 125 g tapioca flour adding 500 g blood clam meat. The analysis parameters observed were organoleptic / hedonic, proximate analysis and heavy metal Pb, Cd. Blood clam meatballs with different amounts of binder that consumers liked are 75 g (69 panelists / 86.25%) of binder with yellowish brown appearance characteristics, chewy and compact texture, slightly distinctive taste of blood clams and distinctive aroma of blood clams. with a moisture value of 63.48%, ash 1.54%, protein 13.95%, and fat 1.70%. Metal content of Pb 0.0199 mg / k and Cd 0.0629 mg / kg.Keywords: blood shells, meatballs blood shells.